Purification of Egg White Lysozyme from Indonesian Kampung Chicken and Ducks - Zakiah Wulandari; Dedi Fardiaz; Cahyo Budiman; Tuti Suryati; Dian Herawati (Faculty of Animal Science, Bogor Agricultural University, 2015)
Egg white lysozyme (EWL) has considerably a wide functional protein exhibiting antibacterial activity mainly against Gram-positive bacteria. The EWL is widely applied in food industry and is considerably safe. Despite its high potency, EWL of Indonesian poultry has never been studied and exploited. This study was aimed to purify EWL from two Indonesian poultry: kampung chicken and Cihateup duck, and compared to egg of commercial laying hens. The eggs in this study were obtained from field laboratory of Faculty of Animal Science, Bogor Agricultural University (IPB) and classified in AA quality based on the interior quality. First attempt to purify the EWL was performed by using ethanol precipitation yielding purified EWL which was still contaminated by other proteins, hence designated as partially purified EWL. Final concentrations of partially purified EWL of kampung chicken, commercial laying hens, and Cihateup duck were about 5800, 5400, and 5500 μg/mL, respectively. To confirm whether the use of ethanol in the purification affecting EWL antibacterial activities, the activities were examined against Staphylococcus aureus. It demonstrated that the partially purified EWL exhibited ability to inhibit S. aureus at 6 and 26 h suggesting that the method was feasible as it did not interfere EWL antibacterial activities. Yet, based on SDS-Page, purity was the issue in ethanol precipitation method. Further attempt using ion exchange chromatography at pH 10 successfully purified lysozyme as indicated by a single band corresponding to lysozyme size ( 14 kD) free from bands of other proteins. Altogether, a single step of ion exchange chromatography is sufficient and promising to isolate EWL from Indonesian poultry for various industrial purposes.Key words: Indonesian poultry, lysozyme, egg, kampung chicken, Cihateup duck